Bacillus subtilis Protects the Ducks from Oxidative Stress Induced by Escherichia coli: Efficacy and Molecular Mechanism - Chong Li; Yang Li; Shuzhen Li; Si Chen; Guohua Liu; Xuejuan Deng; Wenhuan Chang; Huiyi Cai (MDPI AG, 2022)
Bacillus subtilis has been widely used in animal husbandry as a potential alternative to antibiotics due to its excellent bacteriostasis and antioxidant activity. This study aims to investigate the effects of Bacillus subtilis on the protection of ducks from Escherichia coli infection and its mechanism. The four experimental groups include the negative control group, positive control group, antibiotic group and Bacillus subtilis group. Ducks in positive, antibiotic and Bacillus subtilis groups are orally administered with Escherichia coli and equivalent saline solution for the negative group. The results show that supplements with Bacillus subtilis enhances the performance and health status of the infected ducks. Moreover, Bacillus subtilis alleviates the increase in globulin, LPS and MDA, and the decrease in albumin, T-AOC and T-SOD in the serum caused by Escherichia coli infection. Bacillus subtilis also attenuates injury in the intestine and partially reverses the increase in ROS production and the depletion of ATP in the jejunum. These effects are accompanied with the change of related genes of the ribosome (13.54%) and oxidative phosphorylation (6.68%). Collectively, Bacillus subtilis alleviates the damage caused by Escherichia coli infection in ducks by activating ribosome and oxidative phosphorylation signaling to regulate antioxidant and energy metabolism.